Prevalence of depression, anxiety, and substance‐related disorders in parents of children with cerebral palsy: a systematic review. (5th August 2019) - Barreto, Tainara M; Bento, Mayara N; Barreto, Tamiris M; Jagersbacher, João Gabriel; Jones, Nathalia S; Lucena, Rita; Bandeira, Igor D
Abstract : Aim: To estimate the prevalence of mental illness in parents of children with cerebral palsy (CP). Method: This is a systematic review that follows the Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols in the search for observational studies determining the prevalence of depression, anxiety, and substance abuse in parents of individuals with CP. The information sources used for this study were: PubMed, SciELO, Cochrane Library, Clinical Trials, and Biblioteca Virtual de Saúde. Results: Fourteen articles were selected and included, investigating 1264 mothers and 105 fathers of children with CP. Data extracted for analysis were divided into three categories: study data, data about participants with CP, and data about parents. All studies included volunteer parents, of whom 95 per cent were female. Interpretation: CP is related to a higher prevalence of symptoms of depression and anxiety in parents. Factors such as a child's degree of functionality and socioeconomic level may influence the frequency of mental disorders in parents. However, these studies have heterogeneous samples and applied different criteria to characterize their populations. What this paper adds: Depression and anxiety are more prevalent for parents of children with cerebral palsy (CP) than parents of typically developing children. The child's illness severity is a risk factor for mental illness in parents of children with CP. The more time spent on child care, the higher the risk of mental illness among mothers of children with CP. There is a lack of reliable data in the literature on substance abuse in parents of children with CP. What this paper adds: Depression and anxiety are more prevalent for parents of children with cerebral palsy (CP) than parents of typically developing children. The child's illness severity is a risk factor for mental illness in parents of children with CP. The more time spent on child care, the higher the risk of mental illness among mothers of children with CP. There is a lack of reliable data in the literature on substance abuse in parents of children with CP. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Gillberg on page 154 of this issue. Resumen: Prevalencia de depresión, ansiedad y trastornos relacionados al uso de sustancias en padres de niños con parálisis cerebral: Revisión sistemática: Objetivo: Calcular la prevalencia de enfermedad mental en padres de niños con parálisis cerebral (PC). Metodo: Esta es una revisión sistemática que sigue la metodología para Protocolos de Revisiones Sistemáticas y Metaanálisis en la búsqueda de estudios observacionales que determinan la prevalencia de depresión, ansiedad y abuso de sustancias en padres de individuos con PC. Las fuentes de información utilizadas para este estudio fueron: PubMed, SciELO, LILACS, Biblioteca Cochrane, Clinical Trials, y Biblioteca Virtual de Saúde. Resultados: Se seleccionaron e incluyeron 14 artículos, investigando 1.264 madres y 105 padres de niños con PC. Los datos extraídos para análisis fueron divididos en tres categorías: datos de estudio, datos sobre participantes con PC y datos sobre padres. Todos los estudios incluyeron padres voluntarios, de quienes el 95% fueron del sexo femenino. Interpretación: La PC está relacionada a una mayor prevalencia de síntomas de depresión y ansiedad en los padres. Factores como el grado de funcionalidad del niño y el nivel socioeconómico pueden influir en la frecuencia de trastornos cognitivos en los padres. Sin embargo, estos estudios tienen muestras heterogéneas y utilizaron diferentes criterios para caracterizar a las poblaciones. Resumo: Prevalência de depressão, ansiedade, e desordens relacionadas ao uso de substâncias em pais de crianças com paralisia cerebral: uma revisão sistemática: Objetivo: Estimar a prevalência de doença mental em pais de crianças com paralisia cerebral (PC). Método: Esta é uma revisão sistemática que segue o protocol Itens preferenciais para reportar em revisões sistemáticas e metanálises na busca por estudos observacionais que determinassem a prevalência de depressão, ansiedade, e abuso de substâncias nos pais de indivíduos com PC. As fontes de informação usadas para este estudo foram: PubMed, SciELO, LILACS, Cochrane Library, Clinical Trials, e Biblioteca Virtual de Saúde Resultados: Quatorze artigos foram selecionados e incluídos, investigando 1264 mães e 105 pais de crianças com PC. Os dados extraídos para análise foram divididos em três categorias: dados dos estudos, dados sobre os participantes com PC, e dados sobre os pais. Todos os estudos incluíram pais voluntários, dos quais 95 por cento eram mulheres. Interpretação: A PC se relaciona com maior prevalência de sintomas de depressão e ansiedade em pais. Fatores como grau de funcionalidade da criança e nível socioeconomico podem infuenciar a frequência de desordens cognitivas nos pais. No entanto, estes estudos têm amostras heterogêneas e aplicaram diferentes critérios para caracterizar suas populações.